2009
DOI: 10.1016/j.cgh.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Bowel Preparation for Colonoscopy

Abstract: Background & Aims An inadequately cleansed colon can lead to missed lesions, repeat procedures, increased cost, and complications from colonoscopy. Because obesity, with its known link to colorectal neoplasia, might be associated with inadequate bowel cleansing, we investigated the impact of increased body mass index (BMI) on quality of bowel preparation at colonoscopy. Methods All colonos-copy procedures performed at a tertiary referral center during a 4-month period were evaluated. Bowel preparation was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
100
6
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 20 publications
17
100
6
3
Order By: Relevance
“…In most publications, randomized clinical trials investigated the quality of bowel cleansing using various preparations, but few studies were designed to identify factors associated with failure. Among recently published papers, we found observational studies [7][8][9][10]12,27,28 but no case-control studies, which makes our work original and relevant for clinical application. The gastroenterologists enrolled were representative of French gastroenterologists for the type of activity and sex ratio: 73% had a private practice while 27% had a public hospital-based practice, and these data are similar with those of the whole French gastroenterologist population according to a professional French database (CEGEDIM) including 3720 gastroenterologists.…”
Section: Discussionmentioning
confidence: 99%
“…In most publications, randomized clinical trials investigated the quality of bowel cleansing using various preparations, but few studies were designed to identify factors associated with failure. Among recently published papers, we found observational studies [7][8][9][10]12,27,28 but no case-control studies, which makes our work original and relevant for clinical application. The gastroenterologists enrolled were representative of French gastroenterologists for the type of activity and sex ratio: 73% had a private practice while 27% had a public hospital-based practice, and these data are similar with those of the whole French gastroenterologist population according to a professional French database (CEGEDIM) including 3720 gastroenterologists.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the reported predictors of inadequate colon preparation were male gender, inpatient status, and older age (Hassan et al, 2012, Borg et al, 2009, Chan et al, 2011, Chung et al, 2009, Lebwohl et al, 2010, Ness et al, 2001). In our study, incomplete cleansingagent ingestion and patient's unrecognization of vegetable avoidance were independently associated inadequate colonic preparation.…”
Section: Discussionmentioning
confidence: 96%
“…Bunun nedenleri arasında işlem zamanı, hastaların kullanım talimatlarına uyumu, hastanede yatışı, kabızlık endikasyonu, erkek cinsiyet, inme öyküsü, obezite ve yetersiz barsak hazırlığının olduğu bildirilmiştir. (5,6) Biz bu çalışmada, kolonoskopi işlemi öncesi yetersiz kolon hazırlığını önleyebilmek için oral ve lavman yoluyla sağlanan kolon temizliğinin etkinliğinin ve hastaların uyumunun değerlen-dirilmesini amaçladık.…”
Section: Discussionunclassified